2005
DOI: 10.1177/1558925005os-1400202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Processing Conditions on Melt Blown Web Structure: Part 2 -Primary Airflow Rate

Abstract: We are continuing an effort to quantitatively measure the influence of processing variables on the detailed structure of commercial polypropylene melt blown (MB) webs. In this paper, we report the influence of primary airflow rate on fiber entanglement, global fiber orientation and pore structure in webs. This enabled us to quantify the influence of primary airflow on web structural features as well as achieve greater understanding of the commercial MB process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The web consisting of finer fibers usually had a better BWU. In the study of Bresee et al, finer fibers were usually observed in the higher air jet velocity. The pores between finer fibers were evenly distributed in the fibrous web.…”
Section: Resultsmentioning
confidence: 86%
“…The web consisting of finer fibers usually had a better BWU. In the study of Bresee et al, finer fibers were usually observed in the higher air jet velocity. The pores between finer fibers were evenly distributed in the fibrous web.…”
Section: Resultsmentioning
confidence: 86%
“…Irrespective of increase in distance, the molten state of the polymer melt was maintained by the air temperature, which contributed to the formation of finer fibers. These findings were opposite to the effect of increasing the die to collector distance during melt blowing process [21,22]. The reason for such a discrepancy was attributed to the constant air temperatures in the case of this new process which allows the stretching to continue.…”
Section: Optimizationmentioning
confidence: 76%
“…Jamfibers accumulation in space due to adhesion between fiber segments (see Figure 17) occurring during fiber speed decrease through the majority of the die to collector distance, which contributes to fiber disorientation and creation of entanglements between the fibers [14,18,147]. It was concluded that increase in DCD or decrease in air flow rate leads to more entanglements due to more time for fiber contact/entanglement/fusion [82,83,158]. On the other hand, opposite trend was reported by Lee & Wadsworth (1990) [55] and Yesil & Bhat (2016) [76], i.e.…”
Section: Please Cite This Article As Doi:101063/15116336mentioning
confidence: 99%